Acceptability and Feasibility of Hair and Salivary Biomarker Collection Among Multiethnic School‑Age Children - Condon, Eileen M. (Matern Child Health J, 2020)
OBJECTIVE: As noninvasive biological markers gain increasing popularity in pediatric research, it is critical to understand how study participants perceive these measures, especially among groups underrepresented in biobehavioral research, like children and people of color. The purpose of this study was to examine acceptability and feasibility of hair and salivary biomarker collection in an urban community sample of ethnically diverse children (age 4 to 10 years). METHODS: Ninety-seven mother–child dyads were recruited for a cross-sectional follow up study of the Minding the Baby® home visiting intervention. Children were Hispanic (63%), Black (34%), and multi-racial (3.1%). A conventional content analysis was conducted using two sources of data: (1) mothers’ responses to open-ended interview questions on their views and suggestions regarding biomarker collection, and (2) field notes recorded by investigators. RESULTS: Forty-four percent of mothers reported biomarker-related questions or concerns, including questions about the purpose of biomarker testing, and concerns about cosmetic issues, child discomfort, and future use of biomarker data. Mothers also offered positive feedback and advice for collection. Issues affecting feasibility included children’s hair length and style, refusal to participate, and behavioral or developmental issues. CONCLUSIONS: Hair and salivary biomarker collection was largely acceptable and feasible in this sample. Strategies for promoting ethical and sensitive biomarker collection include respectful explanations and parental involvement, creating a comfortable and safe environment for the child, flexible collection strategies, and attention to development, cultural preferences and perspectives.